(3cjajI GSJNQGL hab GdeNeS NGdj GdhSWs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3eUWai Hf jhfS s)
(3ChdgG (B:s
(3EPG QeJ GdCehQ GdegeI Ydjc HNGdj GdLha aj cd SGYI s
(3BNQgG (B:s
(3hUdjH ahbg CQHY fbW hGdLejY ebWYI GdCMQa JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3hGdeNWhW gh aUd ef cdGe GdTjN oeMjj GdOjf efXhekGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeQcRjI GdYGeI (B- (3HZOGO (B(453) s
Keywords: (3GdMQha h GdChaGbs